The influence of parental perfectionism and parenting styles on child perfectionism - Carmo, Claudia (2021)
Perfectionism is a significant transdiagnostic process related to the development and maintenance of several psychological disorders. The main models of the development of perfectionism focus on early childhood experiences and postulate that parental relation is an important factor for understanding this construct in children. The purpose of this study was to examine the relationship between child and parental perfectionism, seeking to evaluate the empirical support of the Social Learning Model and the Social Expectations Model and children’s perception of parenting styles. The present study included 119 children (51.2% girls, Mage = 11.67 years) and their parents. Data were collected through administration of several self-report measures. The results show a relationship between the majority of the same parent and child perfectionism dimensions, thus providing supportive evidence for the Social Learning Model. Concerning the analysis of the role of gender in the transmission of perfectionism, observed fathers’ perfectionism only relates with the sons’ perfectionism, and mothers’ perfectionism relates with daughters’ perfectionism. Our findings allow for a deeper understanding of the role of the perception of an authoritarian parenting style in the development of maladaptive perfectionism. Mother and fathers’ perceived parenting styles contribute more to daughter than son perfectionism. The results contribute to expanding the understanding of the role of parental factors in the development of perfectionism.